The improved hamming number method to detect isomorphism for kinematic chain with multiple joints - Wei SUN; Jianyi KONG; Liangbo SUN (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2017)
During the process of kinematic structure enumeration using graph theory, isomorphism identification of graphs is an important and complicated problem. In this paper, an improved hamming number method (IHNM) was proposed to detect isomorphism for kinematic chain with multiple joints. Firstly, it is difficult to deal with multiple joints in mechanism analysis and synthesis, so the joint-joint matrix is used to describe the kinematic chain. The matrix can uniquely represent the kinematic chain. Then, the improved Hamming matrix is obtained by the improved hamming number method. The joint Hamming number, chain Hamming number and joint Hamming string were introduced, which can determine whether the kinematic chain is isomorphic or not. Eventually, the examples demonstrate that this new method can be accurately and effectively performed.